Characterization of Nest Architecture of an Indian Ant Diacamma indicum (Hymenoptera: Formicidae). Issue 6 (22nd November 2019) - Bhattacharyya, Kushankur; Annagiri, Sumana
Abstract: Nests are physical entities that give shelter to the inhabitants from natural adversities, predators and act as a platform for organization of tasks particularly in social insects. Social insect nests can range from simple structures consisting of a single entrance leading to a chamber to complex nests containing hundreds of connected shafts and chambers. This study characterizes nest architecture of a tropical ponerine ant Diacamma indicum (Hymenoptera: Formicidae), which has small colony sizes and is known to be a scavenger. We also examined if these nests vary seasonally. By examining the microhabitat in the vicinity of the nest, the nest entrance characteristics and casting 77 natural nests of D. indicum across a year, we found that this species occupies relatively simple nests consisting of a single entrance that leads to a single chamber. This chamber progressed to a secondary tunnel that terminated at a greater depth than the chamber. The nest volume was not correlated to the number of adult members in the colony. Even though the microhabitat around the nest and the entrance itself change across seasons, principle component analysis showed that the nest architecture remained similar. Only one parameter, the entrance tunnel showed significant difference and was longer during postmonsoon. Nests of colonies living in the immediate vicinity of human habitation were comparable to other nests. We conclude that D. indicum found in the Gangetic plains live in relatively simple nests that do not vary across seasons.